Financial Management Practices and Coffee Cooperatives Performance in Ethiopia with Mediation of Human Capital - Mershaye Birhane; Chalchisa Amentie; Brehanu Borji; Shashi Kant (iRASD Journal of Management)
The study's main topic was how Ethiopian coffee cooperatives' financial management practices and organizational performance are mediated by human capital. The cross-sectional study with multistage sampling was employed by the researchers. KMO was employed as a test for adequate data. To evaluate the overall impact of the regression, total variance was used. To determine if the observable variables could adequately explain the latent determinants, confirmatory factor analysis was utilized. The model fitness and mediation analysis were both tested using SEM. According to study, there was a significant link based on the data because the KMO value of.906 was greater than 0.5 and the statistical threshold for the Bartlett's test was lower than 0.05. The researchers discovered that the CMIN/DF was less than 3.0, indicating model acceptance. The model being tested is compared using the Tucker Lewis Index (TLI). Mediation of Human capital has led to a roughly 75% boost in performance of Coffee Cooperatives. As a result, there is now some partial mediation between financial management practices and coffee cooperative performance.